2010
DOI: 10.1158/1541-7786.mcr-09-0375
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor–Induced Heparanase Nucleolar Localization Augments DNA Topoisomerase I Activity in Brain Metastatic Breast Cancer

Abstract: Identification of molecular mechanisms responsible for brain metastatic breast cancer (BMBC) is imperative to develop novel therapies. However, current understanding of the molecular circuitry that governs BMBC dissemination remains fragmentary. Heparanase (HPSE) is the only functional mammalian endoglycosidase whose activity correlates with cancer metastasis, angiogenesis, and the reduced post-operative survival of cancer patients, making it an active target for anti-cancer therapeutics. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 28 publications
1
63
0
Order By: Relevance
“…S1D). Interestingly, a recent study showed that topoisomerase I activity was augmented in a breast cancer cell line following epidermal growth factor induced elevation of heparanase in the nucleolus (31). Although the mechanism of heparanase-induced augmentation of topoisomerase I was not examined in this study, it will be interesting to determine if it is related to reduced levels of heparan sulfate present within the nucleolus of these cells.…”
Section: Restoration Of High Syndecan-1 Level In Nucleus Decreasesmentioning
confidence: 86%
“…S1D). Interestingly, a recent study showed that topoisomerase I activity was augmented in a breast cancer cell line following epidermal growth factor induced elevation of heparanase in the nucleolus (31). Although the mechanism of heparanase-induced augmentation of topoisomerase I was not examined in this study, it will be interesting to determine if it is related to reduced levels of heparan sulfate present within the nucleolus of these cells.…”
Section: Restoration Of High Syndecan-1 Level In Nucleus Decreasesmentioning
confidence: 86%
“…Because heparanase plays a role in cell invasion through the degradation of HSPG in the ECM and BM (18,19), we tested the effect of heparanase RNAi on the invasive ability of HepG2 cells using the Matrigel invasion assay. As shown in Fig.…”
Section: Heparanase Sirna Significantly Inhibits the Invasive Abilitymentioning
confidence: 99%
“…Some MMPs have been more thoroughly investigated than others, for example MMP1 has been observed to regulate the levels of transforming growth factor α which in turn affects the activation of EGFR in breast cancer cells [140]. EGFR is relevant to breast cancer as its ligand has been linked to promoting heparanase function and topoisomerase I localization in brain metastasizing breast cancer cells [141]. This information can then facilitate our medical community in development of drugs and treatment, however, to improve it is vital that we pinpoint which MMPs the most critical in breast cancer and how they function during tumor development.…”
Section: Each Variation Of Mmp Has Unique Functionmentioning
confidence: 99%